2010
DOI: 10.2136/sssaj2008.0190
|View full text |Cite
|
Sign up to set email alerts
|

In‐Field Variability of Soil Test Phosphorus and Implications for Agronomic and Environmental Phosphorus Management

Abstract: Spatial and seasonal variability of P presents a challenge for accurate soil sampling for agronomic and environmental management of farm fields. Our objectives were to: (i) evaluate the accuracy of soil sampling protocols (sampling intensity) during the growing season and after harvest, with and without manure application; and (ii) evaluate the impact of temporal and spatial variability on the accuracy of conversion equations for Mehlich‐3 to Morgan P soil test P. Two 4‐ha corn (Zea mays L.) fields were sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…The results of this study suggest that (i) the accuracy of Mehlich-3 to Morgan soil test conversion equations is predominantly influenced by temperature-driven changes in pH and Ca and moisture-impacted changes in Al and that (ii) moisture and temperature impact the accuracy of the Mehlich-3 to Morgan STP conversion models. These observations are consistent with Grandt et al (2010), who reported that sampling time (summer vs. fall) greatly impacted the accuracy and bias of the Mehlich-3 P to Morgan STP conversion equations, and with the very low ratio of measured Morgan to predicted Morgan STP for Soil 1Y3, reflecting its long history of poultry layer litter and the presence of free calcium carbonate (eggshells). For soils with a long-term history of poultry manure application, current Mehlich-3 to Morgan soil test conversion models reported by Ketterings et al (2002) are unreliable because of the dissolution of free calcium carbonate with the Mehlich-3 extraction method.…”
Section: Song and Ketteringssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study suggest that (i) the accuracy of Mehlich-3 to Morgan soil test conversion equations is predominantly influenced by temperature-driven changes in pH and Ca and moisture-impacted changes in Al and that (ii) moisture and temperature impact the accuracy of the Mehlich-3 to Morgan STP conversion models. These observations are consistent with Grandt et al (2010), who reported that sampling time (summer vs. fall) greatly impacted the accuracy and bias of the Mehlich-3 P to Morgan STP conversion equations, and with the very low ratio of measured Morgan to predicted Morgan STP for Soil 1Y3, reflecting its long history of poultry layer litter and the presence of free calcium carbonate (eggshells). For soils with a long-term history of poultry manure application, current Mehlich-3 to Morgan soil test conversion models reported by Ketterings et al (2002) are unreliable because of the dissolution of free calcium carbonate with the Mehlich-3 extraction method.…”
Section: Song and Ketteringssupporting
confidence: 90%
“…2). Similar results were found in a study with calcareous soils in central New York (Grandt et al, 2010), where the most reliable conversions were obtained when soils were sampled after harvest of corn but before manure spreading. A total of 58% of the variability in ratio (measured/predicted) in our study was explained by moisture content (P = 0.0804), whereas temperature was not a significant factor in the stepwise regression.…”
Section: Field Studysupporting
confidence: 86%
“…Moisture content impacted the change in the ratio of measured Morgan to predicted Morgan STP levels for one of the three soils only (Soil 1Y1) mostly as a result of an increase in Morgan STP without significant changes in Mehlich-3 P, Ca, Al, or pH for this pasture soil. These observations are consistent with Grandt et al (2010), who reported that sampling time (summer vs. fall) greatly impacted the accuracy and bias of the Mehlich-3 P to Morgan STP conversion equations, and with the very low ratio of measured Morgan to predicted Morgan STP for Soil 1Y3, reflecting its long history of poultry layer litter and the presence of free calcium carbonate (eggshells). causing the ratio of measured Morgan to predicted Morgan STP to be soil specific as well (P = 0.091).…”
Section: Song and Ketteringssupporting
confidence: 90%
“…In contrast to NO 3 –N, P has much lower mobility in fertility‐limited soils and a high degree of spatial dependence; hence, P is likely to be a better candidate for grid‐based sampling. Several factors may amplify the spatial variability of P. Hot spots from manure application or old homesteads can either increase (Cambardella & Karlen, ) or decrease (Grandt, Ketterings, Lembo, & Vermeylen, ) spatial variability. Surficial or deep‐banding of P fertilizer can increase lateral (Kitchen, Westfall, & Havlin, ) and vertical stratification (Rehm, Scobbie, Randall, & Vetsch, ) of P and K, although the patterns of stratification depend on the tillage system used.…”
Section: Development Of a Soil Sampling Planmentioning
confidence: 99%